Efektivitas Model Permainan Kartu Indeks (Index Card Match) Terhadap Hasil Pembelajaran Perkembangan Kognitif Dan Bahasa Anak Usia 5-6 Tahun Di TK Al-Harits - Andri Pratama; Fatmawati (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the effectiveness of the index card match card game on the cognitive and language development of children aged 5-6 years at AL-Harits Kindergarten. Using qualitative methods and data collection techniques using interviews and direct observations in the field as well as observations of events that occur in the field. The population is all children as many as 40 people. Data analysis used is phenomenal analysis with interviews and observations of children and teachers. The results of the study indicate that the effectiveness of the index card match card game on the cognitive and emotional development of children aged 5-6 years can shape children's mindsets in solving a problem and being more sensitive in making decisions for themselves and of their own wishes in the form of examples, practices, and responsibilities from teachers. It can be concluded that with this index card game, children can make their independence in solving a problem that occurs to themselves and children are more responsible for the decisions they have taken themselves. Keywords: Effectiveness; Index card match; Cognitive and emotional children.